Effect of Suspended Particles on Thermosolutal Convection of Rivlin-Ericksen Fluid in Porous Medium with Variable Gravity - Aggarwal A.K. (International Journal of Applied Mechanics and Engineering, 2018)
The thermosolutal stability of a layer of the Rivlin-Ericksen fluid in a porous medium is considered under varying gravity conditions. It is found that for stationary convection, medium permeability and suspended particles have a destabilizing/stabilizing effect when gravity increases/decreases. The stable solute gradient has a stabilizing effect on the system.